2017
DOI: 10.1016/j.addbeh.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Peer drug use and adolescent polysubstance use: Do parenting and school factors moderate this association?

Abstract: Aims This study examined the association between peer drug use and adolescent polysubstance use, and investigated if this association was moderated by parenting and/or school factors. MethodsThe sample consisted of 9,966 participants (mean age = 14.3; 49.34% males) randomly selected from secondary schools in Victoria, Australia. Three 30-day polysubstance use profiles were derived from latent class analysis -no drug use (47.7%), mainly alcohol use (44.1%) and polysubstance use (8.2%). These profiles were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 17 publications
(17 reference statements)
3
35
1
2
Order By: Relevance
“…The finding that peer deviance mediates the relationship between child maltreatment and adolescent substance use is consistent with studies, which have found that greater levels of deviant peer affiliation are correlated with adolescent substance use (Chan et al, 2017;Fergusson et al, 2002;Zhu et al, 2016). This finding also supports this study's theoretical framework because deviant peers, by virtue of their very deviance, are more likely to engage in substance use.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding that peer deviance mediates the relationship between child maltreatment and adolescent substance use is consistent with studies, which have found that greater levels of deviant peer affiliation are correlated with adolescent substance use (Chan et al, 2017;Fergusson et al, 2002;Zhu et al, 2016). This finding also supports this study's theoretical framework because deviant peers, by virtue of their very deviance, are more likely to engage in substance use.…”
Section: Discussionsupporting
confidence: 90%
“…The strong effect of deviant peer affiliation on adolescent substance use has also been consistently reported (Chan, Kelly, Carroll, & Williams, 2017;Fergusson, Swain-Campbell, & Horwood, 2002;Zhu et al, 2016). Monahan, Rhew, Hawkins, and Brown (2014) examined the developmental patterning of delinquency, substance use, and co-occurring problems (i.e., substance use and delinquency) over time, as well as how deviant peer affiliation was associated with the transitions between incidents (i.e., single substance use or delinquency, as well as co-occurring problems).…”
Section: Child Maltreatment Deviant Peer Affiliation and Substancmentioning
confidence: 89%
“…Limited research has found that situational (e.g., lack of adult supervision, alcohol availability, and lack of enforcement) and social (e.g., group size) context characteristics contribute to increased adolescent alcohol use (Bersamin et al, 2016; Grune et al, 2017; Jackson et al, 2016; Lipperman-Kreda et al, 2015). Characteristics of drinking or substance use contexts may influence alcohol or substance use and problems through increased access and opportunities to engage in risky behaviors (Flewelling et al, 2013; Ryan et al, 2010) or through social modeling, social pressure, or social norms (Chan et al, 2017; Handren et al, 2016). If we understand the situational and social contexts in which young people are likely to use substances simultaneously and experience problems, we can develop interventions that target use and risks within these contexts.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used data from the National Drug Strategy Household Survey (NDSHS), the largest nationally representative household survey in Australia, to: Estimate the prevalence of non‐medical use of pharmaceutical opioids in the Australian population in two types of opioid users—those who predominantly use opioids only and those who use opioid in addition to other illicit substances, because some studies suggest that these two groups are substantially different . Examine the socio‐demographic (such as gender, age, employment status, etc.—see Method section), psychological, health, and behavioural correlates (such as smoking status and alcohol risk) of these two types of opioid user. These variables are selected because they have been found to be associated with other substance use, such as alcohol , tobacco , cannabis , amphetamine and polysubstance use in the Australian population. …”
Section: Introductionmentioning
confidence: 99%
“…Examine the socio-demographic (such as gender, age, employment status, etc.-see Method section), psychological, health, and behavioural correlates (such as smoking status and alcohol risk) of these two types of opioid user. These variables are selected because they have been found to be associated with other substance use, such as alcohol [14,15], tobacco [16,17], cannabis [18], amphetamine [19] and polysubstance use [20][21][22] in the Australian population.…”
Section: Introductionmentioning
confidence: 99%